(untitled) (Research, Society and Development, 2021)
The analysis of the characteristics of the landscape is the first step in the planning and proper management of natural resources. In view of the above, this study aims to provide information on landscape characteristics in the Paraíso river microbasin, Western Amazon, Brazil. The information is associated with geometric, topographic and hydrographic parameters, and ground cover dynamics, and was obtained using the QGIS, Google Earth and TrackMaker Free software, altimetric images (ALOS satellite) and ground cover (Landsat 5 and Landsat 8 satellites), and data from the literature. The Paraíso river microbasin has an area of 50.76 km2, elongated shape, low susceptibility to flooding, altitudes between 234 and 458 m, predominance of wavy relief, medium sized river, 5th order dendritic drainage pattern, high spring density, very high drainage density, meandering main channel, low maintenance coefficient and high concentration time. In the period from 1984 to 2020, agriculture advanced over the areas of native forest, reaching 80.32% of the microbasin area and 64.21% of the riparian area in the last year. The microbasin has a high potential for the development of agricultural systems, however it is recommended to adopt conservationist soil and water management practices, the maintenance and / or recovery of native forests protected by law, and the integration of the tree component in economic systems ( ex: agroforestry and agrosilvipastoral systems). These recommendations aim to reconcile economic development and the conservation of natural resources, both essential for the sustainable development of the region.